2017
DOI: 10.1097/aud.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

Can You Hear What I Think? Theory of Mind in Young Children With Moderate Hearing Loss

Abstract: Children with MHL have more difficulty in their ToM reasoning than hearing peers, despite the fact that their language abilities lie within the average range compared with test normative samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
1
16
0
3
Order By: Relevance
“…In contrast, significantly fewer CHH (41%) demonstrated the same level of understanding as a comparison group of CNH. The results suggest that a sizeable subgroup of CHH were delayed in FB understanding at age 5 years, which supports the findings of Netten et al (2017). In both this study and Netten et al, FB understanding was delayed in spite of CHH performing broadly within the average range on norm-referenced language measures.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, significantly fewer CHH (41%) demonstrated the same level of understanding as a comparison group of CNH. The results suggest that a sizeable subgroup of CHH were delayed in FB understanding at age 5 years, which supports the findings of Netten et al (2017). In both this study and Netten et al, FB understanding was delayed in spite of CHH performing broadly within the average range on norm-referenced language measures.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, only one study has examined the ToM development in a contemporary group of CHH with early service access. Netten et al (2017) measured a variety of ToM skills, including first-order FB in a group of 3-to 5-year-old children with moderate hearing loss (35-70 dB HL) compared with hearing peers. All CHH used spoken language to communicate.…”
Section: Fb Development In Chh Using Hasmentioning
confidence: 99%
See 1 more Smart Citation
“…While early access to language might be associated with ToM gains, some studies suggest that children who are DHH with a language level similar to that of hearing children still show ToM delays. For example, in the study by Netten et al (2017), children with moderate hearing loss (MHL) demonstrated difficulties in some aspects of ToM despite being within the normal range on standardized tests of spoken language. Similarly, Ketelaar, Rieffe, Wiefferink and Frijns (2012) found that children who are DHH with CIs were delayed in ToM even after controlling for verbal ability, and despite having received an implant before the age of 2 years on average.…”
Section: Language and Tom In Children With Hearing Lossmentioning
confidence: 99%
“…The exposure to this complex abstract language is not only beneficial for children's language development, but also for their social-emotional development. This is especially of interest in children with MHL since they encounter difficulties in their social-emotional development (Dirks et al, 2017;Laugen, Jacobsen, Rieffe, & Wichstrom, 2016Netten et al, 2015Netten et al, , 2017. Talking with children about their own and others' thoughts, desires, and feelings promotes their social-emotional development (Devine & Hughes, 2018;Drummond, Paul, Waugh, Hammond, & Brownell, 2014;Dunn, Brown, Slomkowski, Tesla, & Youngblade, 1991;Meins, 2013;Peterson & Slaughter, 2003).…”
Section: Parental Linguistic Inputmentioning
confidence: 99%